Application of critical thinking in teaching Islamic subjects / Syuhaida Idha Abd Rahim, Siti Noorbiah Md Rejab and Mohd Dani Muhamad - Abd Rahim, Syuhaida Idha; Md Rejab, Siti Noorbiah; Muhamad, Mohd Dani (Academy of Contemporary Islamic Studies, 2015)
This study examined the application of critical thinking in teaching Islamic subjects at the campus of Universiti Teknologi MARA Puncak Alam. The sample of this study consisted of students from various faculties. Based on specific characteristics, the researchers used stratified random sampling to draw the samples. In particular, the study examined respondents' perception on critical thinking towards the teaching approaches and methods in teaching critical thinking. Using questionnaire as instrument, this study probed on respondents' view on their lecturers' teaching practices in the aspect of critical thinking. The researchers employed descriptive statistics to analyse the collected data. Findings indicated that the majority of the respondents have positive perceptions on critical thinking. Most of them believed that their lecturers practiced critical thinking in the classroom. They agreed that the use of critical thinking will enhance their success in the off-the-campus activities. Nevertheless, this study does not capture details of the lecturers' actual practices in teaching critical thinking to their students. Perhaps further study using qualitative methods such as classroom observations and interviews with the lecturers would better explain such application of critical thinking in the lecturers' method of teaching.